Love, culture, rationality, and learning in repeated games - Cendales, Andrés; López-Montenegro, Luis Eduardo; Guerrero-Sierra, Hugo (Frontiers in Sociology, 2025)
The dynamics within romantic relationships reflect and influence broader family structures. This article examines family dynamics by analyzing various social identities and power structures, such as gender and social class, through a rational choice methodological approach. It challenges the notion that past family stability was due to stronger values, arguing instead that it was supported by oppressive structures, primarily patriarchal. By critiquing these power structures, we aim to present a more inclusive and equitable perspective on family dynamics. We introduce a rational choice model from game theory to analyze stability patterns in romantic relationships, focusing on empathy coefficients and cultural factors. This model investigates the role of economic altruism theory and cultural identities in shaping empathy and their impact on relationships. The study also explores individual wellbeing across different cultural contexts, including representations of courtly love and patriarchal norms. An instrumental rationality perspective is proposed to address the irrationality of love from a rational standpoint in family literature. Simulation is crucial for validating the model and evaluating the assumptions in realistic contexts. It provides insights into the model's behavior under various conditions, highlighting limitations and aspects previously unconsidered. This approach is essential for verifying implementation, validating assumptions, and exploring data uncertainties. By employing this methodology, future research can gain a deeper understanding of the complexities in family dynamics and romantic relationships.